Solution of the dark matter riddle within standard model physics: from black holes, galaxies and clusters to cosmology - Nieuwenhuizen, Theodorus Maria (Frontiers in Astronomy and Space Sciences, 2024)
It is postulated that the energy density of the (quantum) vacuum acts firstly as dark energy and secondly as a part of dark matter. Assisted by electric fields arising from a small charge mismatch in the cosmic plasma, it can condense on mass concentrations. No longer participating in the cosmic expansion, this constitutes “electro-aether-energy” (EAE), “electro-zero-point-energy” or “electro-vacuum-energy”, which solves the dark matter riddle without new physics. A radial electric field of 1 kV/m is predicted in the Galaxy. For proper electric fields, EAE can cover the results deduced with MOND. An instability allows a speedy filling of dark matter cores. Hydrostatic equilibrium in galaxy clusters is obeyed. Flowing in aether energy of explains why black holes become supermassive, do not have mass gaps and overcome the final parsec problem. Rupture of charged clouds reduces, e.g., the primordial baryon cloud to the cosmic web. The large coherence scale of the electric field acts as a scaffold for gentle galaxy formation and their vast polar structures. In galaxy merging and bars, there occurs no dynamical friction. At cosmological scales, EAE acts as pressureless dark matter. Its amount increases in time, which likely solves the Hubble tension by its late time physics. A big crunch can occur. Of the large cosmological constant injected at the Big Bang, a small part kept that form, without fine-tuning.